PENGARUH PRINSIP CORPORATE SOCIAL RESPONSIBILITY TERKAIT DENGAN IKLIM INVESTASI MENURUT UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL DAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - JULIA AGNETHA AGNESTA Br. BARUS; BUDIMAN GINTING; MAHMUL SIREGAR (TRANSPARENCY, 2013)
The activity of capital investment as an effort to increase economic growth should be supported by transparent coordination and policy of capital investment in order to create conducive climate. CSR in a corporation is a legal responsibility which should be implemented by the corporation. According to Law No. 25/2007 on Capital Investment a conducive investment climate can be realized when there are legal certainty and certainty for doing business, facility in giving license to investors, good political condition in the State, and low economic cost for the benefit of the investors. The implementation of CSR in a corporation can be known when the corporation has carried out the principles of responsibility, sustainability, accountability, and transparency and the principles found in ISO 26000. The influence of the principle of Corporate Social Responsibility on the investment climate under Law No. 25/2007 on Capital Investment and Law No. 40/2007 on Corporation is that the implementation of CSR by a corporation can make reciprocal relationship which will be mutually beneficial for its stakeholders. CSR will give positive implication for increasing people’s welfare, creating conducive investment climate, reducing cost, helping develop the government, strengthening business investment, and strengthening the partnership among the people, the government, and the business world. If this condition can be realized, investors will be interested in investing their capital in the corporation which carries out CSR in Indonesia. Kata kunci :     Prinsip, Corporate Social Resposibility (CSR), Investasi.